Water balance profiles, humidity preference and survival of two sympatric cockroach egg parasitoids Evania appendigaster and Aprostocetus hagenowii (Hymenoptera: Evaniidae; Eulophidae). (June 2015) - Tee, Hui-Siang; Lee, Chow-Yang
Graphical abstract: Highlights: A. hagenowii had lower cuticular permeability than E. appendigaster . All wasps lost water at similar rates, except male A. hagenowii at a higher rate. Females of both species showed an overlapping preference for the wettest chamber. A. hagenowii preferred a drier area, which was least preferable by E. appendigaster . Humidity preference in both species is likely to be related to their life history. Abstract: The impact of desiccation on habitat selection, foraging and survival has been characterized for many insects. However, limited information is available for parasitic wasps. In this study, water balance, relative humidity (RH) preference, and effect of humidity on survival of solitary Evania appendigaster (L.) (Hymenoptera: Evaniidae) and gregarious Aprostocetus hagenowii (Ratzeburg) (Hymenoptera: Eulophidae) were examined. These species are both oothecal parasitoids of the American cockroach Periplaneta americana (L.) (Dictyoptera: Blattidae). E. appendigaster had significantly higher cuticular permeability (CP) and a lower surface area to volume ratio but a similar percentage of total body water content compared to A. hagenowii . No differences in these attributes were found between sexes of each parasitoid species. The percentage of total body water loss rates among E. appendigaster males and females and A. hagenowii females were similar but significantly lower than that of A. hagenowii males. All parasitoids except E. appendigaster males exhibited reduced survival times as the RH of their enclosure decreased from 87% to 38%, but this phenomenon did not occur when parasitoids were given a sugar solution. In environmental chambers with a 44–87% RH gradient, both sexes of E. appendigaster resided significantly more often in the 87% RH chamber than in the 44% RH chamber. For A. hagenowii, females preferred both the driest and the wettest chambers and males preferred the driest ones. These results demonstrate the water balance profile and its relationship to life history traits and differential responses to RH in these competing parasitoid wasps, suggesting the role of physiological and behavioral adaptations in shaping their ecological niche.